TEORI BELAJAR KOGNITIF DENGAN MEDIA KARTU KATA DALAM MENINGKATKAN LITERASI MEMBACA SISWA KELAS 1 - Nurul Hidayati; Sri Dewi Nirmala (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to examine the extent to which cognitive learning theory combined with word cards can improve the reading literacy skills of first-grade students at UPTD SD Negeri 3 Mengandung Sari. The main problem underlying this study is the low interest and basic reading skills of students in the early stages of elementary school. The cognitive approach was chosen because it focuses on mental activities such as information processing, conceptual understanding, and systematic knowledge formation, making it very suitable for the needs of early reading learning that requires high concentration. Word cards are used as visual aids to strengthen the relationship between letter symbols, syllable sounds, word forms, and their meanings in a concrete manner. This study uses a qualitative descriptive method by collecting data through participatory observation during learning, in-depth interviews with class teachers, and assessment of students' reading abilities before and after the implementation of the action. The research findings show that the use of word cards has a significant impact on improving students' skills in recognizing letters, combining syllables, and reading simple words more fluently. Students' cognitive involvement is seen through activities such as grouping words by category, matching words with pictures, and doing independent repetition to strengthen long-term memory. From a pedagogical perspective, word cards support concrete learning and are aligned with the concrete operational developmental stage of early childhood. Psychologically, students appear more confident, enthusiastic, and motivated because the reading process is packaged into a fun and easy-to-understand activity. Thus, the integration of cognitive learning theory through word cards has proven effective in accelerating reading.